기록관리 전문가단체의 교육 서비스 방향 모색을 위한 탐색 연구: 한국기록전문가협회를 중심으로 - 김혜영; 이경남; 김장환; Kim, Hyeyoung; Lee, Kyoungnam; Kim, Janghwan (Journal of Records Management & Archives Society of Korea, 2022)
This study aims to identify the current situation and core competencies of records managers and archivists through an in-depth interpretation of the perception and its meaning behind their experiences and, based on them, to seek the educational service directions of professional organizations. As a result of qualitative data analysis using interpretive phenomenological research method, this study identified three categories of field needs, core competencies, and educational service directions, as well as 10 super-topics, 30 sub-topics, and 82 semantic units. Based on this, this study has suggested the educational service directions of professional organizations, such as the provision of opportunities to secure external driving forces for work innovation, the provision of learning opportunities for communication and public discussion among institutions, and the provision of new partnerships and practical learning opportunities. This study is meaningful in having derived the main educational service directions that professional organizations should focus on and support by identifying the current situation and core competencies of records managers and archivists. 본 연구는 기록관리 전문직의 경험 이면에 있는 인식과 그 의미를 해석하여 현재 처한 상황과 핵심 역량을 도출하고, 이를 토대로 전문가단체의 교육 서비스 방향을 모색하는 데 목적이 있다. 해석현상학적 연구방법을 통한 질적 데이터 분석 결과, 본 연구는 기록관리 현장의 요구 상황, 기록관리 전문직 핵심 역량, 교육 서비스 방향의 3개 범주와 10개 상위주제, 30개의 하위주제와 82개의 의미단위를 생성하였다. 이를 기반으로 전문가단체의 교육 서비스 방향으로, '업무 혁신을 위해 외부 동력을 확보할 수 있는 기회 제공', '기관 간 소통 및 공론화를 위한 학습 기회 제공', '새로운 파트너십과 실질적인 학습 기회 제공'을 제시하였다. 본 연구는 현재 기록관리 전문직이 처한 상황 속에서 실질적으로 요구 받고 있는 핵심 역량을 파악함으로써 전문가단체가 집중하여 지원해야 할 주요한 교육 서비스 방향을 도출하였다는 데 그 의의가 있다.